The effect of site of origin on fatty acid percent in sunflower oil (Helianthus annuus L) - Baghdad Science Journal (مجلة بغداد للعلوم)
A Laboratory study was conducted in quality control department ,state company for food stuff trading ministry of trade (2005-2006) on sunflower oil imported to Iraq from different origins included 12 trade marks, Complete random design was used with four replication .The purpose of the study is to know the origins effect on fatty acid percent and study the simple correlation between them, the result showed Turkish origin for trademark (Narin) was superior in Palmitic and Stearic fatty acid (10.41,3.29%).While Omanian origin for trademark Alsafwa was superior in Oleic(35.09%) and Syrian origin for trade mark Alnahraen was superior in Linoleic fatty acid percent 66.53% whereas Egyptian origin for trademark Alasel was superior in the percentage of un saturation with 1.62% . We concluded from this study that fatty acids Oleic and Linoleic were the major fatty acid in sunflower and increase in their percentage determine the type and quality of sunflower especially Linoleic fatty acid which is belong to Omega -6 family and its cannot made in human body .